Relationship Between Heavy Metal levels in Seminal Plasma and Sperm Quality in Iranian Men - Heidari Khoei, Heidar; Ziarati, Niloofar; Karimi Dehkordi, Maryam; Rezaei Tobbraghale, Tohid; Taher mofrad, Mohammad Javad; Azizi, Elham; Fakhri, Yadolah; Shams Mofarahe, Zahra (Archives of Men's Health, 2021)
Introduction: During the last decades, frequent reports on the poor semen quality in humans have raised many researchers' concerns to study the possible impact of lifestyle or environmental factors on semen quality. The debate is continuously growing on the adverse reproductive effects of exposure to heavy and trace metals found in the environment, even at their relatively low levels. Materials and Methods: This study was carried out from July 2018 to February 2019. A total of 40 men were divided into two groups (idiopathic oligo– and/or asthenozoospermia and normozoospermic men) to determine the correlation between arsenic (As), cadmium (Cd), copper (Cu), and manganese (Mn) levels in the seminal plasma with sperm quality parameters including concentration, total motility, progressive motility, viability, mitochondrial membrane potential (MMP), sperm plasma membrane integrity (SPMI), acrosome integrity (AI) and DNA fragmentation in Iranian men with idiopathic oligo– and/or asthenozoospermia and normozoospermic individuals. Results: A significant positive or suggestive correlation was found between as concentrations in the seminal plasma and sperm concentration, motility, progressive motility, viability, MMP, SPMI, and DNA fragmentation. Moreover, seminal plasma Cd concentrations were also correlated negatively with sperm viability. We also found a positive correlation between the seminal plasma Mn levels and sperm concentration, motility, progressive motility, morphology, viability, acrosome integrity, and DNA fragmentation. Conclusion: We showed that the levels of As, Cd, and Mn levels in the seminal plasma are associated with the sperm functional parameters. Considering the unpleasant effects of the studied metals on semen quality, it is suggested that long-term contact with these metals be avoided, especially by people at their reproductive age.